2003
DOI: 10.1046/j.1365-2133.2003.05093.x
|View full text |Cite
|
Sign up to set email alerts
|

Atopy patch test reactions to Malassezia allergens differentiate subgroups of atopic dermatitis patients

Abstract: Atopy patch test reactions to Malassezia allergens differentiate subgroups of atopic dermatitis patients.Johansson, C.; Sandström, M.H.; Bartosik, Jacek; Särnhult, T.; Christiansen, J; Zargari, A.; Bäck, Ove; Wahlgren, C.F.; Faergemann, J.; Scheynius, A.; Tengvall Linder, M. Link to publication Citation for published version (APA): Johansson, C., Sandström, M. H., Bartosik, J., Särnhult, T., Christiansen, J., Zargari, A., ... Tengvall Linder, M. (2003). Atopy patch test reactions to Malassezia allergens diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 40 publications
5
86
0
2
Order By: Relevance
“…When combining APT and in vitro peripheral blood analysis on 64 AE patients, we found that a majority of the AE patients reacted to the investigated allergen M. sympodialis in accordance with previous reports [17, 24]. The number of peripheral T cells responding to M. sympodialis by IL-4 production was correlated with the APT score and was, if above a certain level, predictive for a positive APT reaction.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…When combining APT and in vitro peripheral blood analysis on 64 AE patients, we found that a majority of the AE patients reacted to the investigated allergen M. sympodialis in accordance with previous reports [17, 24]. The number of peripheral T cells responding to M. sympodialis by IL-4 production was correlated with the APT score and was, if above a certain level, predictive for a positive APT reaction.…”
Section: Discussionsupporting
confidence: 70%
“…But in contrast to this proposed mechanism, the relationship between AE patients’ allergen-specific plasma-IgE levels and their skin reactivity is not clear. Positive APT reactions are found both in patients with intrinsic AE [14, 29] and in extrinsic AE patients lacking detectable IgE against the allergen in question [11, 14, 16, 24, 29]. This could possibly be explained by the need for a minimal amount of circulating allergen-specific IgE, and/or local IgE production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin prick tests were first used in the diagnosis of this allergy. The literature results are recapitulated in table 2 [12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22]. In all the studies except one [21], the percentage of skin prick test positivity was higher in patients with HNAD than in patients with non-HNAD.…”
Section: Discussionmentioning
confidence: 68%
“…A Swedish multicenter study of 132 subjects with AD revealed that 60% had a positive skin test response to Malassezia species in comparison with no positive test responses in the non-atopic subjects [42].…”
Section: Immunologic Triggers Bacteria Viruses Fungimentioning
confidence: 99%